Differences in Opinions About Marijuana Use and Prevalence of Use by State Legalization Status. Issue 4 (July 2020) - Steigerwald, Stacey; Cohen, Beth E.; Vali, Marzieh; Hasin, Deborah; Cerda, Magdalena; Keyhani, Salomeh
Abstract : Objective: Beliefs about marijuana use and prevalence of use may be associated with the legalization status of the state of residence. We examined differences in views and rates of use of marijuana among residents in recreationally legal, medically legal, and nonlegal states. Methods: We surveyed a nationally representative online panel of US adults (N = 16, 280) and stratified results by marijuana legalization status of states. We compared views of residents of recreational states on benefits and risks of marijuana use to residents in other states. Results: The response rate was 56.3% (n = 9003). Residents in recreationally legal states were more likely to believe marijuana could be beneficial for pain management (73% in recreationally legal states, 67% in medically legal states, 63% in nonlegal states; P value: <0.0001), provide relief from stress, anxiety or depression (52% in recreationally legal states, 47% in medically legal states, 46% in nonlegal states; P value: 0.01), and improve appetite (39% in recreationally legal states, 36% in medically legal states, 33% in nonlegal states; P value: <0.009). In addition, residents in recreational states were significantly more likely to believe that smoking 1 marijuana joint a day is somewhat or much safer than smoking 1 cigarette a day (40.8% in recreationally legal states, 39.1% in medically legal states, and 36.1% in nonlegal states; P value: <0.0001). Residents of recreationally and medically legal states were more likely to believe second-hand marijuana smoke was somewhat or much safer than second-hand tobacco smoke (38.3% in recreationally legal states, 38.3% in medically legal states, and 35.7% in nonlegal states; P value: 0.003). Past-year marijuana use in any form (20% in recreational, 14.1% in medical, 12% in nonlegal) and past-year marijuana use of multiple forms (11.1% in recreational, 6.1% in medical, 4.9% in nonlegal) were highest among residents of recreationally legal states. Overall, prevalence of past-year use of any form of marijuana use was more common among residents of recreationally legal states compared with other states (20.3%, confidence interval [CI] 19.5, 21.1 in recreationally legal states; 15.4%, CI 14.7, 16.2 in medically legal states; 11.9%, CI 11.2, 12.6 in nonlegal states). Conclusions: Residents in recreationally legal states were most likely to believe marijuana has benefits, marijuana smoke is safer than tobacco smoke, and have the highest rate of marijuana use. This is cause for concern, given the tide of commercialization, growing number of high-potency cannabis products, and favorable media coverage promoting use for health problems. Abstract : Supplemental Digital Content is available in the text